The Effectiveness of the Project Based Learning Model on Writing Skills in Senior High Schools - Citra Agustina; Sumarno (Universitas Pendidikan Ganesha, 2026)
Writing skills are an important indicator of literacy competence in senior high school. However, writing instruction is still largely conventional, limiting students’ ability to express ideas systematically, creatively, and critically. This study aims to examine the effectiveness of project-based learning in improving students’ writing skills in senior high school.This study employed a Systematic Literature Review (SLR) approach, involving an in-depth analysis of scientific articles published between 2021 and 2025. This SLR was conducted to gather the latest empirical evidence, minimize bias, and synthesize findings from various sources. The literature search was conducted through Google Scholar using keywords such as